Ergonomic Safety Approach for Welding Activities of Piping Installation - Bin Nazeri, Muhammad Akmal; Syahrun Niezam Bin Mohd Dzulkifli (Progress in Engineering Application and Technology, 2023)
A case study on the approach of ergonomic safety concept towards work improvement was explored in the welding workshop of Enproserve (M) Sdn Bhd to complete one of the evaluations, Project Bachelor.   The main research objective is to observe discomfort working posture during welding at Enproserve (M) Bandar Penawar using Questionnaire based on WERA checklist. The proposed method for this study will contribute to new knowledge in the ergonomic research field, especially to knowledge of methods in ergonomic exposure assessment tools. It has had a significant impact on employees' comfort, which has a direct impact on the effectiveness and productivity of their job. The workers have alleged that they experience painful postures and injuries at work. The most prevalent issue that employees usually describe is musculoskeletal disorders (MSDs). This issue arises from workers' awareness of and inattention to the ergonomics of their environment.